Evaluation Using COBIT 5 to Determine IT Resource Governance Capability Level: A Case Study of Bank DKI - Athallah, Rafi; Sardjono, Wahyu (Budapest International Research and Critics University, 2022)
With the rapid growth of their business, Bank DKI wanted to utilize their IT usage to the upmost maximum. One of the methods to make sure that the IT Resources perform as expected is by routine evaluation. By Using COBIT 5 as a framework to evaluate the maturity level of IT resource, researcher can determine on how capable the performance and reliability of the IT resources is present within Bank DKI. Researcher found that problems arose for the company especially on managing the IT resources which may cause Bank DKI to suffer losses of important company assets. With the expected capability level from Bank DKI of level 3 (established), researcher is conducting a measurement of IT resource governance and found that Bank DKI is still at capability level 1 (performed).